Palatability profile in spontaneously hypertensive rats - Pereira, Emilson Donizete [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José Vanderlei [UNESP]; Andrade, Carina Aparecida Fabrício [UNESP] (Oxford University Press (OUP), 2023)
The spontaneously hypertensive rats (SHRs) have enhanced palatability for NaCl taste as measured by the increased number of hedonic versus aversive responses to intraoral infusion (1 mL/1 min) of 0.3 M NaCl, in a taste reactivity test in euhydrated condition or after 24 h of water deprivation + 2 h of partial rehydration (WD-PR). SHRs also ingested more sucrose than normotensive rats, without differences in quinine hydrochloride intake. Here, we investigated the palatability of SHRs (n = 8–10) and normotensive Holtzman rats (n = 8–10) to sucrose and quinine sulphate infused intraorally in the same conditions that NaCl palatability was increased in SHRs. SHRs had similar number of hedonic responses to 2% sucrose in euhydrated condition (95 ± 19) or after WD-PR (142 ± 25), responses increased when compared with normotensive rats in euhydrated condition (13 ± 3) or after WD-PR (21 ± 6). SHRs also showed increased number of aversive responses to 1.4 mM quinine sulphate compared with normotensive rats, whether in euhydrated condition (86 ± 6, vs. normotensive: 54 ± 7) or after WD-PR (89 ± 9, vs. normotensive: 40 ± 9). The results suggest that similar to NaCl taste, sweet taste responses are increased in SHRs and resistant to challenges in bodily fluid balance. They also showed a more intense aversive response in SHRs to bitter taste compared with normotensives. This suggests that the enhanced response of SHRs to taste rewards does not correspond to a decreased response to a typical aversive taste.
Keywords: dehydration; hypertension; quinine; sucrose; taste